The heart of a chief - Bruchac, Joseph, 1942- (Puffin Books, 2001)
An eleven-year-old Penacook Indian boy living on a reservation faces his father's alcoholism, a controversy surrounding plans for a casino on a tribal island, and insensitivity toward Native Americans in his school and nearby town.